2010
DOI: 10.1590/s1516-89132010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits the growth and stimulates the lignification of soybean root

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
(38 reference statements)
0
22
0
2
Order By: Relevance
“…Quercetin and naringenin were reported as the most often cited allelopathic flavonoids (Berhow and Vaughn (1999)). Naringenin was reported to inhibit the growth of soybean (Bido et al 2010). These bioactive compounds might play a role in the allelopathic activity of R. tingitana either singular or in a synergetic manner.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin and naringenin were reported as the most often cited allelopathic flavonoids (Berhow and Vaughn (1999)). Naringenin was reported to inhibit the growth of soybean (Bido et al 2010). These bioactive compounds might play a role in the allelopathic activity of R. tingitana either singular or in a synergetic manner.…”
Section: Resultsmentioning
confidence: 99%
“…Within the flavonoids class, naringenin is a flavanone that derives from naringin or narirutin (its glycone precursor) hydrolysis [5]. In fact, naringenin occupies a central position as primary C 15 intermediate in the flavonoid biosynthesis pathway [6]. Naringenin biosynthesis has been investigated in Medicago , parsley and other plants.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory effect of Nar was attributed at least to some extent, through impaired auxin transport. Deng et al (2004) suggested that it exert its inhibitory effect by inhibiting the activity of the key enzyme of the phenylpropanoid pathway, 4-coumarate: CoA ligase, whereas Bido et al (2010) assumed that the action site of naringenin may be related to other enzymes working at later steps of the phenylpropanoid pathway, such as cell wall-bound POX or, perhaps, cinnamyl alcohol dehydrogenase. Hence, the mode of action of naringenin still remains an open question in plant systems.…”
Section: Introductionmentioning
confidence: 99%